13C NMR chemical shifts in substituted benzenes: analysis using natural perturbation orbitals and substitution effects. (19th March 2021) - Miyamoto, Masaya; Hada, Masahiko
Abstract : The natural perturbation orbital (NPO) method, combined with the gauge-including atomic orbital (GIAO), was applied to nuclear magnetic resonance (NMR) chemical shifts. The substituent effects of electron-donating (NH2 ) and electron-withdrawing (NO2 ) groups on the 13 C NMR chemical shifts of monosubstituted benzenes were analysed using NPOs. 13 C chemical shifts at the ortho -, meta - and para -positions were efficiently decomposed into contributions from two NPO pairs ( σ x − π x ∗, σ y − π y ∗ ). These contributions were further divided into two factors, namely electron density in the vicinity of resonance nuclei and orbital energy gaps. Trends in the electron density matched with the ortho -, meta - and para -directions of the substituent effects. Specifically, NH2 shielded the ortho - and para -carbons, while NO2 deshielded the same carbons. The orbital energy gaps of ortho -carbons in NH2 - and NO2 -benzenes were significantly decreased, showing that these substituents shielded the ortho -carbons. GRAPHICAL ABSTRACT: